CURRICULUM DESIGN OF MU'ADALAH IN ISLAMIC BOARDING SCHOOLS: CASE STUDY AT ANNUR DARUNNAJAH ISLAMIC BOARDING SCHOOL 8 - Nabila Putri Maulida; Bahrissalim Bahrissalim; Akhmad Sodiq (LP2M IAI Al-Khairat Pamekasan, 2026)
Islamic boarding School are Islamic educational institutions that play a strategic role in shaping the character, morality, and intellect of the Muslim generation. The development of the times and the demands of integration with the national education system have encouraged pesantren to develop a curriculum that is not only oriented towards mastery of religious knowledge, but also responsive to modern needs. This study analyzes the mu'adalah curriculum design at Islamic boarding School Annur Darunnajah 8, focusing on the aspects of planning, implementation, evaluation, and the impact of its application on improving the quality of pesantren education. The study uses a qualitative case study approach, with data obtained through observation, in-depth interviews, and documentation. The results show that the mu'adalah curriculum is designed independently through the integration of the national curriculum, the salafiyah Islamic boarding School tradition, and the Tarbiyatul Mu'allimin al Islamiyah (TMI) system. The implementation of intracurricular, co-curricular, and extracurricular activities is carried out in an integrated manner to achieve a balance between religious competence and general knowledge. Education based on classical Islamic texts is combined with the concepts of mu'adalah salafiyah and mu'allimin. Learning evaluation is carried out in stages by caregivers and teachers through an academic examination system and character assessment. The impact of implementing this curriculum includes flexibility in learning, strengthening Arabic and English language skills, shaping character and discipline, improving leadership and cooperation, developing skills through supporting activities, opportunities for further study abroad, and expanding national and international partnership networks. In addition, the character building of santri is strengthened through the internalization of the concept of “The 7 Habits of Highly Effective People.” The study concludes that the mu'adalah curriculum design in this Islamic boarding school is effective in improving the quality of education and producing graduates who are adaptive to the times.